Novel Systems and Membrane Technologies for Carbon Capture - Eshorame Samuel Sanni; Emmanuel Rotimi Sadiku; Emeka Emmanuel Okoro (International Journal of Chemical Engineering)
Due to the global menace caused by carbon emissions from environmental, anthropogenic, and industrial processes, it has become expedient to consider the use of systems, with high trapping potentials for these carbon-based compounds. Several prior studies have considered the use of amines, activated carbon, and other solid adsorbents. Advances in carbon capture research have led to the use of ionic liquids, enzyme-based systems, microbial filters, membranes, and metal-organic frameworks in capturing CO2. Therefore, it is common knowledge that some of these systems have their lapses, which then informs the need to prioritize and optimize their synthetic routes for optimum efficiency. Some authors have also argued about the need to consider the use of hybrid systems, which offer several characteristics that in turn give synergistic effects/properties that are better compared to those of the individual components that make up the composites. For instance, some membranes are hydrophobic in nature, which makes them unsuitable for carbon capture operations; hence, it is necessary to consider modifying properties such as thermal stability, chemical stability, permeability, nature of the raw/starting material, thickness, durability, and surface area which can enhance the performance of these systems. In this review, previous and recent advances in carbon capture systems and sequestration technologies are discussed, while some recommendations and future prospects in innovative technologies are also highlighted.